Entre Paris et les Tropiques, le rôle inattendu des Instituts Pasteur dans la naissance de la psychologie animale pendant la période coloniale - Marion Thomas (Revue de Primatologie)
This article explored the unexpected connections between the Pasteur Institutes of Paris and Kindia (French Guinea) and the study of animal mind and behaviour in the second quarter of the twentieth century France. At a time animal intelligence was blooming in France and elsewhere, apes became not only an attractive research model for psychological studies, but also were appealing to biomedical studies. This article shows how the Pastorian bacteriologist Albert Calmette played a pivotal role in the emergence of animal psychology by providing the psychologists with apes, both in the colonies and the metropole. With the help of Calmette, the psychologists Paul Guillaume and Ignace Meyerson in Paris, on the one hand, and the American psychologists Robert Yerkes et Henry Nissen in French Guinea, on the other hand, made the best of the conditions offered by the Pasteur Institutes to study respectively the chimpanzee mind in the laboratory and its behaviour in the wild. However, attempts to use apes to yield new insights on animal psychology faced heavy restrictions or experienced false starts, and this article examines the reasons why animal psychology could not properly thrive at that time in France and Guinea. Beyond the supremacy of biomedical interests over psychological ones, this article additionally explains that, in France, some individuals used animal behaviour studies as steppingstones in careers in which they proceeded on to other topics. Then, between the metropole and the Tropics, the laboratory and the field, this article examines how the long reach of biomedicine (linked to the prestige of Bernard and Pasteur) impinged on French biology and played a role in the development of animal psychology (and animal ethology) within the Pasteur Institutes in the second quarter of the twentieth century.